Application of a novel heterogeneous sulfite activation with copper(i) sulfide (Cu2S) for efficient iohexol abatement. Issue 13 (11th March 2022) - Wu, Ying; Xing, Danying; Zhang, Linna; Suo, Hualiang; Zhao, Xiaodan
Abstract : The Cu2 S/sulfite process achieves efficient iohexol abatement, in which reductive sulfur species prominently accelerate Cu species' redox cycle and radical generation. Abstract : Transition metal ion-activated sulfite autoxidation processes for the production of sulfate radicals (SO4 ˙ − ) have been widely investigated to achieve efficient abatement of recalcitrant organic pollutants. However, these homogeneous processes suffered from narrow effective pH range and metal release, thus restricting their practical application. In order to address this problem, we report a simple and efficient approach to iohexol abatement by a combined Cu2 S and sulfite process (simplified as Cu2 S/sulfite process) based on the superior activation performance of copper and the excellent electron donating capacity of the low-valent sulfur species. Compared with typical copper oxides, Cu2 S can significantly accelerate the sulfite autoxidation to generate radicals, leading to 100% iohexol abatement in the Cu2 S/sulfite process. The influence of solution pH and dissolved oxygen on iohexol abatement is also investigated. Qualitative and quantitative analysis of reactive radicals is performed by electron paramagnetic resonance (EPR) and radical quenching experiments. Generation of SO4 ˙ − from sulfite activation with Cu2 S mainly contributes to the iohexol abatement. X-ray photoelectron spectroscopy (XPS) suggests that copper is the main activation site and the reductive sulfur species can achieve the continuous regeneration of copper. Application potential of the Cu2 S/sulfite process is also assessed. This study provides a new method for the treatment of water and wastewater containing organic micropollutants.